Platinum Nanoflower-Modified Electrode as a Sensitive Sensor for Simultaneous Detection of Lead and Cadmium at Trace Levels - Thi Lieu Nguyen; Van Hoang Cao; Thi Hai Yen Pham; Truong Giang Le (Journal of Chemistry)
We introduce the fabrication and electrochemical application of platinum nanoflower-modified glassy carbon electrode (PtNFs/GCE) for the trace level determination of lead and cadmium using differential pulse anodic stripping voltammetry (DPASV). The modified electrodes have been characterized by EDX, XRD, SEM, and AFM techniques to confirm chemical and physical properties. The effect of potential electrodeposition on the properties of the electrode was investigated. At −0.2 V of potential, platinum developed with a nanoflower shape and dispersed densely all over the glassy carbon surface. In this condition, the highest of lead and cadmium electrochemical signals was clearly observed. The sensor showed wide linearity in the concentration range of 1–100 μg·L−1 with detection limits of 0.408 μg·L−1 and 0.453 μg·L−1 for lead and cadmium ions, respectively. The produced electrodes have good reproducibility with relative standard deviations of 4.65% for lead and 4.36% for cadmium ions. The results demonstrate that this simple, stable, and sensitive sensor is suitable for the simultaneous electrochemical determination of Pb2+ and Cd2+ at trace levels.